The optimal piano teacher: Sosniak’s model versus Polish teachers from public music schools - Chmurzyńska, Małgorzata (Interdisciplinary Studies in Musicology, 2018)
The author deals with the relationship between a piano teacher and her/his pupil/student at different stages of development. The relationship is defined in the literature as one of the most important features determining musical-artistic achievements. She describes the American research into the nurturing of pianists’ talent, and presents the optimal model of piano teacher devised by L. Sosniak, based on interviews with 20 young American pianists with high and significant achievements. The model indicates that the best conditions for artistic development are the sequence of three different teachers, or three different pedagogical strategies, adjusted to the stages of development of young musicians: (1) music teacher for the youngest pupils, whose task is to arouse interest and provide intrinsic motivation and passion for music and piano-playing; (2) instructor teacher (for teenagers), whose task is to help students to build a solid métier, acquire the necessary motor skills and piano technique, and to improve their artistic performance; (3) master teacher for young adult pianists, whose task is to help them to integrate the skills gained previously, to shape their artistic personality. This sequence turned out to be extremely favourable for the later achievements of the interviewed pianists. The author then provides an analysis of statements by Polish pianists from the older generation, and an observation of the behaviour of piano teachers from Polish public music schools. These show that in our piano pedagogy there exists only one type of teacher, the instructor teacher who, compared to Sosniak‘s model, places the greatest emphasis on technical skills and avoids the issue of expression.